2012
DOI: 10.2147/ijn.s29710
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol-loaded solid lipid nanoparticles versus nanostructured lipid carriers: evaluation of antioxidant potential for dermal applications

Abstract: Background: Excessive generation of radical oxygen species (ROS) is a contributor to skin pathologies. Resveratrol (RSV) is a potent antioxidant. Solid lipid nanoparticles (SLN) and nanostructured lipid carriers (NLC) can ensure close contact and increase the amount of drug absorbed into the skin. In this study, RSV was loaded into SLN and NLC for dermal applications. Methods: Nanoparticles were prepared by high shear homogenization using Compritol 888ATO, Myglyol, Poloxamer188, and Tween80. Particle size (PS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
139
2
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(159 citation statements)
references
References 35 publications
12
139
2
6
Order By: Relevance
“…Although it seems that there are no statistical differences in polydispersity indices (PDI) between NLC with 5% (PDI 0.280) and 15% (PDI 0.259) oil and the SLN formulation (PDI 0.263), the NLC formulations with 30% (PDI 0.224) and 45% (PDI 0.213) oil showed smaller size distribution than SLN. 32 The comparison of 6 SLN and NLC formulations loaded with different amounts of sildenafil citrate and prepared with identical processes revealed that NLC showed a lower particle size than SLN in all formulations. This observation was attributed to the better emulsification of the solid lipid matrix when oil is incorporated in the solid matrix.…”
Section: Introductionmentioning
confidence: 94%
“…Although it seems that there are no statistical differences in polydispersity indices (PDI) between NLC with 5% (PDI 0.280) and 15% (PDI 0.259) oil and the SLN formulation (PDI 0.263), the NLC formulations with 30% (PDI 0.224) and 45% (PDI 0.213) oil showed smaller size distribution than SLN. 32 The comparison of 6 SLN and NLC formulations loaded with different amounts of sildenafil citrate and prepared with identical processes revealed that NLC showed a lower particle size than SLN in all formulations. This observation was attributed to the better emulsification of the solid lipid matrix when oil is incorporated in the solid matrix.…”
Section: Introductionmentioning
confidence: 94%
“…Membran lipitlerini ve çekirdek DNA'sını oksidatif hasara karşı belirgin ölçüde korur 61 . [80][81][82][83][84][85][86][87][88] . Sentetik ve doğal kökenli kozmetik bileşenleri açısından yeni taşıyıcı sistemlerin kullanımının birçok avantajı vardır.…”
Section: Enzimlerunclassified
“…Sentetik ve doğal kökenli kozmetik bileşenleri açısından yeni taşıyıcı sistemlerin kullanımının birçok avantajı vardır. Bitkisel kökenli bileşenlerin biyoparçalanma ve düşük toksisite gibi bazen avantajlı oldukları durumlar da göz önüne alınarak bitkisel bileşenlerin kozmetik formülasyonlarda kullanımında lipozom, fitozom, transferzom, nanoemülsiyon, nanopartikül, mikroemülsiyon, nanokristal, kübozomlar ve mikrosüngerler ile çalışılmıştır [80][81][82][83][84][85][86][87][88][89][90] . Özellikle nanoemülsiyonlar son yıllarda kişisel bakım ürünlerinde sürekli etkili kozmetikler ve aktif bileşenlerin belli deri katmanlarına dağılmasında tercih edilmektedir.…”
Section: Enzimlerunclassified
See 1 more Smart Citation
“…It is extremely photosensitive compound with low chemical stability, which limits its beneficial therapeutic effects [4]. Thus, loading of resveratrol in nanoporous silica systems can stabilize and protect it from degradation.…”
Section: Introductionmentioning
confidence: 99%